Analysis on the Influence of Urban and Rural Economic Differentiation on the Development of Art Design Teaching - Yike Wang; Lingling Zhang (Discrete Dynamics in Nature and Society)
Art design education in China has nearly 30 years of development history. Due to China’s vast territory, a large population, regional economic development, and social resources are extremely unbalanced, resulting in the uneven development of art design education in various regions. Art design is not only a practical and artistic comprehensive discipline, it also spans more majors. It contains almost all aspects of urban and rural construction, beautification, so its scientific and effective design scheme indirectly affects the future development process of urban and rural economy. First, this paper analyzes the impact of urban and rural economic development on art design teaching. The research results show that it has a great influence and a wide range of influence on art design teaching, including enhancing the naturalness of art discipline, promoting the creativity of art design discipline, and promoting the historicity of art discipline. Second, this paper also analyzes the role of art design in promoting regional economic development. For example, we should make full use of regional cultural differences, expand regional historical elements, pay attention to art design talents, and ensure the supply of funds.